Statins Impair CD1d-Mediated Antigen Presentation Through Inhibition of Prenylation - Khan, Masood A. (2009)
Statins are widely used as cholesterol-lowering agents that also decrease inflammation, and target enzymes essential for prenylation, an important process in the activation and intracellular transport of proteins vital for a wide variety of cellular functions. Here, we report that statins impair a critical component of the innate immune response, CD1d-mediated antigen presentation. The addition of specific intermediates in the isoprenylation pathway reversed this effect, whereas specific targeting of enzymes responsible for prenylation mimicked the inhibitory effects of statins on antigen presentation by CD1d as well as MHC class II molecules. This study demonstrates the importance of isoprenylation in the regulation of antigen presentation and suggests a mechanism by which statins reduce inflammatory responses.